2000
DOI: 10.1103/physrevlett.85.2510
|View full text |Cite
|
Sign up to set email alerts
|

Two Regimes of Asymmetry-Induced Transport in Non-neutral Plasmas

Abstract: Confinement of charged particles in cylindrical Penning-Malmberg traps depends strongly on cross-magnetic-field transport induced by electric and/or magnetic asymmetries. New measurements in pure-electron plasmas demonstrate two separate transport regimes depending on the particle bounce-to-rotation ratio, or rigidity, R identical with&fmacr;(b)/f(E). For R<10, the transport scales as V(a)R-2, where V(a) is the strength of an applied electrostatic asymmetry. For R greater, similar10-20, this " R-2 transport" c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…It was found that tile mobility time T,, depends nearly linearly on the line density, as shown in Fig. 6 (recently, it was found that T,, for "rigid" columns depend linearly on density, but only same-size columns were compared [6] in that study).…”
Section: Asymmetry-dominated Transportmentioning
confidence: 92%
“…It was found that tile mobility time T,, depends nearly linearly on the line density, as shown in Fig. 6 (recently, it was found that T,, for "rigid" columns depend linearly on density, but only same-size columns were compared [6] in that study).…”
Section: Asymmetry-dominated Transportmentioning
confidence: 92%
“…This may indicate a transition to bananaregime scaling, but the data is not sufficient to support this conclusion. Note that there is no dramatic dependence of m on radius, so if we were to calculate the expansion rate Av as in reference [8] the low amplitude scaling would still be 0. Further exploration of our parameter space has found some cases showing scaling closer to 0' and some of these cases are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of such asymmetries would produce a radial component to the E x B drift that would lead to particle loss to the walls of the trap. This suggestion led to a number of experiments [2][3][4][5][6][7][8] employing applied asymmetries in order to study the transport in a controlled manner. Most of the experiments have used electric asymmetries since these are easily applied and manipulated using the sectored wall portions of the confinement region of the trap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it now appears likely that most of the (L/B) −2 lifetime scalings from "background asymmetries" [6] can be given interpretation in terms of the (partially) known scalings for TPM transport. The measurements of transport from applied electric and magnetic asymmetries [7,8,9, 10] also should be compared to TPM predictions. "Anomalous" damping of diocotron modes [7,11,12] is almost certainly related to TPM effects, since TPM damping scales as B −3 .…”
Section: Introductionmentioning
confidence: 99%